A case of anti‐laminin 332 mucous membrane pemphigoid manifesting as desquamative gingivitis. Issue 1 (29th June 2020) - Maeda, Sahoko Imai; Fujiwara, Kumiko; Tomihara, Kei; Yamazaki, Manabu; Imaue, Shuichi; Noguchi, Makoto
Abstract: Anti‐laminin 332 mucous membrane pemphigoid (MMP) is characterized by circulating anti‐laminin 332 autoantibodies, with a high risk of concurrent malignant neoplasms. We report a case of anti‐laminin 332 MMP manifesting as a desquamative gingivitis. A 45‐year‐old woman experienced painful erythema and occasional bullous lesions on the gingiva despite good oral hygiene and plaque control. Intraoral examination revealed gingival inflammation with desquamation. Biopsy showed subepithelial cleft formation suggesting a subepidermal blister. Direct immunofluorescence revealed the deposition of IgG and IgA in the epithelium. Accordingly, we diagnosed anti‐laminin 332 MMP and treated with systemic corticosteroids. The oral lesion resolved after 3 months.